Riders on the Storm - Juan J. Dolado; Álvaro Já\~nez; Felix Wellschmied (Institute of Labor Economics (IZA), 2025)
Online food delivery platforms typically operate through a controversial business model that relies on subcontracting self-employed workers, known as riders. We quantify the labor-market effects of the Spanish Riders' Law in 2021 that established the presumption of dependent employment for riders using a search and matching model. Riders with heterogeneous preferences for leisure trade off work flexibility and easier employability as self-employed against enjoying higher wages as employees. Our main finding is that the reform led to a higher share of employees but failed to fully absorb the large flows of workers transiting out of self-employment and decreased riders' wages leading to welfare losses. However, complementing the reform with a payroll tax cut for platforms hiring employees preserves employment levels and increases riders' welfare.
Keywords: J21; J60; 330; riders; food delivery platforms; self-employed; employees